Significant improvement in portal‐systemic liver failure symptoms and successful management of portal‐splenic venous hemodynamics by the combination of interventional radiology and pharmacotherapy. Issue 10 (15th July 2020) - Ishikawa, Tsuyoshi; Hamamoto, Kaori; Sasaki, Ryo; Nishimura, Tatsuro; Matsuda, Takashi; Iwamoto, Takuya; Takami, Taro; Sakaida, Isao
Abstract : This study describes a case of hepatitis C virus‐related decompensated cirrhosis with portal‐systemic liver failure and refractory encephalopathy. It was successfully managed with a combination of interventional radiology and pharmacotherapy, to improve hepatic function, including hyperammonemia and to control portal‐splenic venous hemodynamics with hepatic venous pressure gradient (HVPG) monitoring. A man in his late 50s presented with a Child–Pugh score of 13, Model for End‐Stage Liver Disease‐sodium (MELD‐Na) score of 19 and blood ammonia level of 185 μg/dL. He underwent balloon‐occluded retrograde transvenous obliteration (BRTO) followed by partial splenic embolization (PSE) and non‐selective beta‐blocker (NSBB) administration. BRTO induced drastic changes in the portal‐splenic venous hemodynamics, resulting in dramatically improved hepatic function and reduced hyperammonemia. However, the procedure resulted in increased HVPG from 13.6 mmHg at baseline to 23.5 mmHg at 1‐month post‐BRTO, accompanied by ascites retention and development of portal hypertensive gastropathy. Thereafter, PSE was performed, followed by NSBB administration, to control the elevated portal venous pressure following BRTO. Postoperatively, the patient's ascites and portal hypertensive gastrophy improved after splenic artery embolization, which eventually disappeared after the additional administration of NSBBs 1 month later. The HVPG finally decreased to 16.9 mmHg; the Child–Pugh score, MELD‐Na score and blood ammonia level improved to 7, 11 and 22 μg/dL, respectively, after all therapies. BRTO significantly improved the symptoms of portal‐systemic liver failure with refractory encephalopathy. PSE and NSBB administration could contribute to additional amelioration of hepatic function and successful management of complications induced by portal hemodynamic changes following BRTO.